Fabrication and characterization of Dy:Y2O3 transparent ceramic phosphor - Lau, Annabel Si Lin (2016)
Interest in transparent ceramics for Light Emitting Diode (LED) has been increasing due to the growing demand for solid-state lightings. The major current method in producing commercialized white LED is the phosphor converted LED made of blue emitting chip and yellow Ce:YAG phosphors dispersed in organic silicone. However, there are several prevailing issues with this current method, such as poor heat resistance of the organic silicone, degradation of phosphor layer in the long run and low colour rendering index due to the mixing of two colours. Thus, to tackle these issues, transparent inorganic ceramic phosphor excited by blue chip is a developing alternative method to the current conventional silicone-based phosphor converter. In this project, 1 at% of Dysprosium (Dy) doped cubic Yttrium oxide (Y2O3) was fabricated by solid state reaction method using high purity commercialized raw materials. To study the effects of sintering temperature on the transparent ceramic products, the green bodies were sintered at three different temperatures, 1780oC, 1830oC and 1880oC. The results were obtained by utilizing different characterization methods to analyze the synthesized transparent ceramics in terms of their relative density, crystal structure, microstructure and the degree of light transmittance. Archimedes’ principle was applied to determine the relative density of (Dy0.01Y0.99)2O3 transparent ceramics. Higher relative density would give greater light output due to lesser light scatter as a result of lower porosity. X-ray diffraction patterns have confirmed that the synthesized transparent ceramic samples is pure Y2O3 cubic structure. Pores were observed from the SEM images and the transparent ceramic samples displayed acceptable degree of light transmittance. From the analysis of these results, it can be concluded that (Dy0.01Y0.99)2O3 transparent ceramic sintered at 1830oC will give the highest quality and quantity of light output due to higher relative density and a microstructure with no pores observed. Therefore, it is vital to determine the optimal sintering temperature to fabricate transparent ceramic that allows high quality and quantity light output to be produced. More research could be done to and several recommendations were also suggested for future research.